Factors Affecting The Choice of Core Earnings Management Tool - Manish Bansal, (Asian Academy of Management Journal, 2024)
Prior studies document that managers manipulate core earnings through different methods to favourably influence the perception of stakeholders towards the operating performance of the firm. However, it is of interest to examine which core earnings manipulation method is preferred by firms because each method needs a different set of opportunities and incentives. The current study explores the methods of core earnings manipulation, namely expense misclassification and revenue misclassification in terms of opportunities and incentives. Results show that the choice of method largely depends on the size and age of the firm. In particular, results exhibit that large and old firms prefer revenue misclassification over expense misclassification for managing core earnings. This effect is found to be more pronounced among large older firms. Our subsequent tests suggest that Big Four auditors (Deloitte, Ernst & Young, KPMG, and PricewaterhouseCoopers) have a constraining effect on expense misclassification, however, they are unable to mitigate the corporate misfeasance of revenue misclassification, implying the partial effectiveness of Big Four auditors in curbing classification shifting. These results are robust to the alternative measurement of misclassification practices and endogeneity issues. The findings have important implications for auditors, analysts, and accounting standard-setters.